Analisis Pertimbangan Hakim Terkait Permohonan Ganti Kelamin Di Pengadilan Negeri Batam (International Forum of Researchers and Lecturers, 2024)
This article explores the judicial considerations and decisionmaking process regarding a petition for gender reassignment at the Batam District Court, exemplified by Case Number 176/Pdt. P/2024/PN Btm. The analysis encompasses legal aspects, presented evidence, principles of justice, and the societal impacts of the court's decision. The study utilizes a descriptiveanalytical approach to examine the legal framework, notably the Law No. 24 of 2013 on Population Administration, and evaluates medical and psychological evidence supporting the petitioner's gender identity. Additionally, comparative analysis of previous cases aids in understanding the application of Indonesian law concerning gender reassignment. The conclusion emphasizes the importance of a fair and legally sound decision that respects societal norms and ensures equitable outcomes for all stakeholders